2017
DOI: 10.1038/srep40243
|View full text |Cite
|
Sign up to set email alerts
|

High-precision, non-invasive anti-microvascular approach via concurrent ultrasound and laser irradiation

Abstract: Antivascular therapy represents a proven strategy to treat angiogenesis. By applying synchronized ultrasound bursts and nanosecond laser irradiation, we developed a novel, selective, non-invasive, localized antivascular method, termed photo-mediated ultrasound therapy (PUT). PUT takes advantage of the high native optical contrast among biological tissues and can treat microvessels without causing collateral damage to the surrounding tissue. In a chicken yolk sac membrane model, under the same ultrasound parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 65 publications
2
55
0
Order By: Relevance
“…We have demonstrated that PUT, as a newly developed antivascular therapeutic method 11 , can non-invasively eliminate microvessels in the choroid in rabbit eyes with excellent efficacy and safety. In comparison with the standard anti-VEGF therapy for wet AMD, PUT removes microvessels through a different mechanism, which is to directly damage vascular endothelial cells through mechanical forces produced via cavitation 11 .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We have demonstrated that PUT, as a newly developed antivascular therapeutic method 11 , can non-invasively eliminate microvessels in the choroid in rabbit eyes with excellent efficacy and safety. In comparison with the standard anti-VEGF therapy for wet AMD, PUT removes microvessels through a different mechanism, which is to directly damage vascular endothelial cells through mechanical forces produced via cavitation 11 .…”
Section: Discussionmentioning
confidence: 96%
“…In comparison with the standard anti-VEGF therapy for wet AMD, PUT removes microvessels through a different mechanism, which is to directly damage vascular endothelial cells through mechanical forces produced via cavitation 11 . Through a single treatment, PUT can largely stop the perfusion in the target area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations